A qualitative exploration of the effects of increasing the minimum purchase age of alcohol in Thailand. (5th July 2012) - Limaye, Rupali J.; Srirojn, Bangorn; Lilleston, Pam; Aramrattana, Apinun; Thomson, Nicholas; Celentano, David D.; Sherman, Susan G.
Abstract Introduction and Aims Although prevalence of alcohol consumption has been relatively stable among Thai youth, concerns over alcohol‐related harms affecting youth influenced the passage of new laws in early 2008, which made it illegal to sell alcohol to anyone under the age of 20. This qualitative study explored the effects of the law on the purchasing patterns of underage Thai bar patrons, in order to understand the strategies employed by underage youth to circumvent the law. Design and Methods A total of 41 in‐depth interviews were conducted with 18‐ to 19‐year‐old bar patrons in Chiang Mai, Thailand. Results Underage Thai bar patrons frequented shops where enforcement was not strict and purchased alcohol from familiar shopkeepers in their neighbourhoods. Participants suggested that purchasing alcohol was relatively easy as long as shopkeepers were driven by the need to make a profit. Discussion and Conclusions To address alcohol‐related harms, the control law must be enforced in a meaningful way to deter youth from purchasing alcohol. Otherwise, the law will have minimal effectiveness in reducing the harms associated with alcohol.